Spectrophotometric Estimation of Ofloxacin in Pure and Pharmaceutical Dosage Forms - Padmanabha Reddy, Y.; Ravindra Reddy, J.; Sowmya, C.; Jaswanth, K.; Hemanth, A. (Asian Journal of Chemistry, 2010)
The present work was aimed to develop a spectrophotometric method in ultraviolet region for the estimation of ofloxacin in pure form and pharmaceutical formulations. Ofloxacin is an antibacterial agent and belongs to the class of fluoroquinolones used in the treatment of respiratory tract infections. Ofloxacin exhibited maximum absorbance at 291.6 nm in 0.1 N hydrochloric acid with an apparent molar absorptivity of 3.175 × 104. Beer's law was obeyed in the concentration range of 1-10 μg/mL. Results of the analysis were validated by recovery studies.